Design, Synthesis and Molecular Docking of Novel Acetophenone-1,2,3-Triazoles Containing Compounds as Potent Enoyl-Acyl Carrier Protein Reductase (InhA) Inhibitors - Fawzia Faleh Albelwi; Hanaa M. Abdu Mansour; Maram M. Elshatanofy; Yeldez El Kilany; Kamal Kandeel; Bassma H. Elwakil; Mohamed Hagar; Mohamed Reda Aouad; El Sayed H. El Ashry; Nadjet Rezki; Maged A. El Sawy (MDPI AG, 2022)
New medications are desperately needed to combat rising drug resistance among tuberculosis (TB) patients. New agents should ideally work through unique targets to avoid being hampered by preexisting clinical resistance to existing treatments. The enoyl-acyl carrier protein reductase InhA of M. tuberculosis is one of the most crucial targets since it is a promising target that has undergone extensive research for anti-tuberculosis drug development. A well-known scaffold for a variety of biological activities, including antitubercular activity, is the molecular linkage of a1,2,3-triazole with an acetamide group. As a result, in the current study, which was aided by ligand-based molecular modeling investigations, 1,2,3-triazolesweredesigned and synthesized adopting the CuAAC aided cycloaddition of 1-(4-(prop-2-yn-1-yloxy)phenyl)ethanone with appropriate acetamide azides. Standard spectroscopic methods were used to characterize the newly synthesized compounds. In vitro testing of the proposed compounds against the InhA enzyme was performed. All the synthesized inhibitors completely inhibited the InhA enzyme at a concentration of 10 µM that exceeded Rifampicin in terms of activity. Compounds 9, 10, and 14 were the most promising InhA inhibitors, with IC50 values of 0.005, 0.008, and 0.002 µM, respectively. To promote antitubercular action and investigate the binding manner of the screened compounds with the target InhA enzyme's binding site, a molecular docking study was conducted.